Validation of handheld fundus camera with mydriasis for retinal imaging of diabetic retinopathy screening in China: a prospective comparison study. Issue 10 (29th October 2020) - Xiao, Baixiang; Liao, Qinghua; Li, Yanping; Weng, Fan; Jin, Ling; Wang, Yanfang; Huang, Wenyong; Yi, Jinglin; Burton, Matthew J; Yip, Jennifer LY
Abstract : Objectives: To investigate the clinical validity of using a handheld fundus camera to detect diabetic retinopathy (DR) in China. Design and settings: Prospective comparison study of the handheld fundus camera with a standard validated instrument in detection of DR in hospital and a community screening clinic in Guangdong Province, China. Participants: Participants aged 18 years and over with diabetes who were able to provide informed consent and agreed to attend the dilated eye examination with handheld tests and a standard desktop camera. Primary and secondary outcome measures: Primary outcome was the proportion of those with referable DR (R2 and above) identified by the handheld fundus camera (the index test) compared with the standard camera. Secondary outcome was the comparison of proportion of gradable images obtained from each test. Results: In this study, we examined 304 people (608 eyes) with each of the two cameras under mydriasis. The handheld camera detected 119 eyes (19.5%) with some level of DR, 81 (13.3%) of them were referable, while the standard camera detected 132 eyes (21.7%) with some level of DR and 83 (13.7%) were referable. It seems that the standard camera found more eyes with referable DR, although McNemar's test detected no significant difference between the two cameras. Of the 608 eyes with images obtained by desktop camera, 598 (98.4%) images were of sufficient quality for grading, 12 (1.9%) images were not gradable. By the handheld camera, 590 (97.0%) were gradable and 20 (3.2%) images were not gradable. The two cameras reached high agreement on diagnosis of retinopathy and maculopathy at all the levels of retinopathy. Conclusion: Although it could not take the place of standard desktop camera on clinic fundus examination, the handheld fundus camera showed promising role on preliminary DR screening at primary level in China. To ensure quality images, mydriasis is required.